A dynamic account of self-efficacy in entrepreneurship - GIELNIK, Michael M. (Institutional Knowledge at Singapore Management University, 2020)
We present a dynamic account of self-efficacy in entrepreneurship that integrates social–cognitive and control theory. According to our dynamic account, variability in self-efficacy energizes action because it involves self-motivation and discrepancy perception as competing motivational processes. We argue that variability and the average level in self-efficacy nascent entrepreneurs display over time support the enactment of entrepreneurial intentions and predict business ownership. The proposed positive effect of variability further implies an inverted u-shaped relationship between self-efficacy at a single point in time and business ownership. To test these hypotheses, we repeatedly assessed entrepreneurial self-efficacy of nascent African entrepreneurs during a 12-week entrepreneurship training program (total N = 241). Twelve months later, we assessed business ownership (total N = 190). We found that variability and the average level in entrepreneurial self-efficacy participants displayed during the training program were positively related to business ownership. Furthermore, for participants with strong entrepreneurial intentions, we found an inverted u-shaped relationship between entrepreneurial self-efficacy after the training program and business ownership. The study suggests that social–cognitive and control theory highlight different facets of self-regulation that both need to be accounted for to explain goal achievement in entrepreneurship.